Determination of Pesticide Residues in Fresh Fruits in the Serbian Market by LC-MS/MS - Isidora Kecojević; Danica Mrkajić; Vladimir Tomović; Biljana Bajić; Milana Lazović; Ana Joksimović; Mila Tomović; Aleksandra Martinović; Dragan Vujadinović; Srđan Stefanović; Vesna Đorđević (Foods)
The concentrations of pesticide residues were determined in 2164 samples of 46 fruit species, collected over a 4-year period. Fruits originated from 59 countries, including Serbia (N = 199). Pesticide residues were determined by liquid chromatography–tandem mass spectrometry (LC-MS/MS) after extraction using a modified QuEChERS protocol. A total of 173 pesticide residues were detected. Of the fruit samples, 62.57% had pesticide residues at or above 0.01 mg/kg, and 4.67% exceeded the maximum residue limits (MRLs) set by the Serbian regulation. MRL values were most often exceeded in pomegranate and citrus fruits (grapefruit and mandarin). The most frequently found pesticide was imazalil (detected in 624 samples, 28.84%), with the highest concentration (93.870 mg/kg) found in a grapefruit sample. Multiple pesticides were detected in 50.92% of the fruit samples, and two grapefruit samples contained up to 44 pesticide residues.